Analisis Pengelolaan Anggaran Pendapatan Belanja Desa (APBDes) (Studi Kasus : Desa Compang Ndehes, Kecamatan Wae Ri'i, Kabupaten Manggarai) - Jena, Marie Teresa Avilla Manbait; Seran, Maria Bernadette Esy; Jaimun, Elfrida Trivonia; Kenas, Familia Fernanda; Dawu, Leopold Melkiano Triangga (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
This study aims to analyze the management of the Village Revenue and Expenditure Budget (APBDes) in Compang Ndehes Village, Wae Ri’i Subdistrict, Manggarai Regency. The research employs a qualitative approach with data collected through interviews and documentation. The focus of the research is to understand the sources of village income and how the budget is utilized for village expenditures. The results show that Compang Ndehes Village generates annual revenue of over IDR 1.4 billion, primarily from transfer funds such as Village Funds (Dana Desa), Village Fund Allocation (ADD), and other financial assistance. The budget is allocated to five main areas: village government administration, village development implementation, community development, community empowerment, and emergency response. Budget planning, implementation, and accountability in Compang Ndehes Village are carried out in accordance with the Minister of Home Affairs Regulation No. 20 of 2018 and the Regent Regulation No. 27 of 2015. The findings indicate that the village government has implemented good financial management principles, namely transparency, accountability, participation, orderliness, and budget discipline. Despite a budget deficit of IDR 7,229,864 in 2024, it was resolved through financing receipts, ensuring no budget shortfall at year-end. The study concludes that the management of APBDes in Compang Ndehes Village is fairly effective but still requires continuous supervision and community involvement to ensure optimal use of funds.